ANALISIS HUBUNGAN BODY IMAGE DENGAN PERILAKU MAKAN DAN STATUS GIZI REMAJA - Rania, Khansa; Hermanto, Restu Amalia; Harfika, Aviani (Journal of Holistic and Health Sciences (Jurnal Ilmu Holistik dan Kesehatan), 2023)
Background : Body Image is a person's perception, thoughts and feelings about theur body. Negative body image of adolescents affects the amount of food intake and nutrients which have an impact on adolescent nutritional status. Meanwhile, the fulfillment of nutrients in adolescents is very important for it is related to the growth and development that occurs during adolescence. Objectives : This study aims to the association Body Image with Eating behaviour and Nutritional Status Of Adolescents Methods : Observational analytic study with 48 subjects who was taken by consecutive sampling, using google form survey media. The nutritional status data was gathered by using Stunkard’s Figure Rating Scale (FSR), the body image data was gathered by using Body Shape Questionnaire (BSQ), and the eating behaviour data was gathered by using Adolescent Food Habits Checklist (AFHC). Results : About 42 subjects (87.5%) have a negative body image and about 6 subjects (12.5%) have a positive body image. 35 subjects (83.3%) with good behaviour have a negative body image, and about 29 subjects (69.9%) with normal nutritional status have a negative body image. There were not significant association between body image and eating behaviour ( p = 0.742). There were significant association between body image and nutritional status ( p = 0.016). Conclusion : There were not significant association body image with eating behaviour of adolescents. There were significant association body image with nutritional status of adolescents.